GIS-based on-road vehicular emission inventory for Lucknow, India - Singh D.; Shukla S.P.; Sharma M.; Behera S.N.; Mohan D.; Singh N.B.; Pandey G. (My University, 2025)
Megacities in India (population more than 10 million) have taken actions to control air-pollution emissions. However, the second-level cities (population between one and 10 million) have not drawn an action plan, and people face serious air pollution in these cities. For one such city, Lucknow, a geographic information system (GIS)-based methodology for emission inventory of on-road vehicles has been developed. The pollutants include: sulfur dioxide (SO2); oxides of nitrogen (NOx); carbon monoxide (CO); particulate matter (PM); 1,3 butadiene; formaldehyde; acetaldehyde; total aldehydes; and total polycyclic aromatic hydrocarbons (PAHs). Video recording was done at nine road intersections of varying land-use patterns to assess traffic count and vehicle kilometer travel. Parking lot surveys were carried out for assessing engine type, vehicle age, etc. and to arrive at a suitable net emission factor for each vehicle category. The 2-wheelers (2-Ws) and 4-wheelers (4-Ws) dominate the total traffic with an 83% share and are main sources of NOx (46%) and CO (77%). The heavy duty vehicles (HDVs: buses and trucks), although they account for only 2% of the vehicle fleet, emit disproportionately high emissions (23% of SO2, 36% of NOx, and 28% of PM). Spatial cell (2×2 km)-wise emission inventory of pollutants indicates that the city center has the highest pollutant emissions resulting from a large number of vehicles, mostly 2-Ws, 3-Ws, and passenger cars. The inventory information can be used for short-term and long-term planning to reduce emissions. © 2014 American Society of Civil Engineers.